2011
DOI: 10.1021/ja208456k
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional, Biocompatible Supramolecular Hydrogelators Consist Only of Nucleobase, Amino Acid, and Glycoside

Abstract: The integration of nucleobase, amino acid, and glycoside into a single molecule results in a novel class of supramolecular hydrogelators, which not only exhibit biocompatibility and biostability, but also facilitate the entry of nucleic acids into cytosol and nuclei of cells. This work illustrates a simple way to generate an unprecedented molecular architecture from the basic biological building blocks for the development of sophisticated soft nanomaterials, including supramolecular hydrogels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 83 publications
4
109
0
Order By: Relevance
“…Furthermore, such a relatively even fi brillar network may greatly benefi t the mechanical properties of RSF/HPMC9 hydrogel, because recent report have suggested that the formation of fi bril bundles could strengthen their mutual interactions, and thus contributed to the enhancement of the mechanical performance of hydrogel. [ 35 ] …”
Section: Fibrillar Network Of Rsf/hpmc9 Hydrogelsmentioning
confidence: 99%
“…Furthermore, such a relatively even fi brillar network may greatly benefi t the mechanical properties of RSF/HPMC9 hydrogel, because recent report have suggested that the formation of fi bril bundles could strengthen their mutual interactions, and thus contributed to the enhancement of the mechanical performance of hydrogel. [ 35 ] …”
Section: Fibrillar Network Of Rsf/hpmc9 Hydrogelsmentioning
confidence: 99%
“…Beside polymer-based gels, a particular class of hydrogels has more recently emerged that is generated by self-assembly of low molecular weight building blocks, which form supramolecular structures under particular physico-chemical conditions. For example, peptide-based gels have been developed that offer a high versatility in terms of chemical modifi cations and hence tuneable biological properties (Li et al, 2011;Matson et al, 2011). Thermosensitive hydrogels have the capacity to form gels as temperature increases above the critical solution temperature, designed to be below body temperature (Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nanofibers of these hydrogelators exhibit significant interbase interactions with nucleic acids, which facilitate single strand oligonucleic acids entering cells and the nuclei of cells. [162] This feature is particularly attractive and warrants further exploration by incorporating different biofunctional peptides or molecular recognition motifs to achieve a wide range of biological functions, such as receptor targeting, nucleic acids condensation, blocking metabolism, endosomal escape, and nuclear localization.…”
Section: Supramolecular Hydrogels Made Of the Hybrids Of Basic Biomentioning
confidence: 99%